1984
DOI: 10.1039/an9840900057
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of ketoprofen and its determination in pharmaceutical dosage forms by differential-pulse polarography

Abstract: A simple differential-pulse polarographic method has been developed for the determination of ketoprofen in dosage forms. Methanol was employed as the solvent for extracting the drug from the formulations, and Britton -Robinson buffer (pH 6.0) containing 5% V/Vmethanol was used as the supporting electrolyte. The EP occurs at -1.15 V. Results obtained by the proposed method are in excellent agreement with those provided by the manufacturer's laboratory. Commonly used tablet excipients and suppository bases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…6). The values found for KP were in good agreement with that previously reported by Amankwa and Chatten (29) in the same conditions. For BP, these values are in the same range as the values found by Nadjo and Savéant (30) in previous experiments performed in acetonitrile solutions in the cavity of an EPR spectrometer.…”
Section: Electrochemical Determinationssupporting
confidence: 92%
“…6). The values found for KP were in good agreement with that previously reported by Amankwa and Chatten (29) in the same conditions. For BP, these values are in the same range as the values found by Nadjo and Savéant (30) in previous experiments performed in acetonitrile solutions in the cavity of an EPR spectrometer.…”
Section: Electrochemical Determinationssupporting
confidence: 92%
“…Analogously to those aromatic ketone derivatives reported in [16][17][18][19][20][21], a single reduction peak of trepibutone at about À1.1 V in a two-electron, two-proton addition was observed in aqueous solution, and two separate peaks were seen in organic medium from two successive one-electron transfers, demonstrating that the free radical occurred [23][24][25]. Obviously, the voltammetric behavior of trepibutone at a PGE was different from that at a mercury electrode, although an aqueous solution was still used as the experimental medium in this work.…”
Section: Voltammetric Behavior Of Trepibutonementioning
confidence: 97%
“…The polarographic behavior of fenofibrate, ketoprofen, amiodarone, mebendazole and flubendazole, all aromatic ketone derivatives, have been studied in aqueous and organic media by Yardimci and Ö zaltin [16], Li et al [17], Amankwa and Chatten [18], Tan et al [19], Pinilla and Hemadez [20] and El-Enamy et al [21], respectively. The results demonstrated that the carbonyl moiety in the benzoyl group in these compounds was electroactive.…”
Section: Voltammetric Behavior Of Trepibutonementioning
confidence: 99%
“…In view of its chemical structure, amiodarone was known as (2-butyl-3-benzofuranyl)[4-[2-(diethylamino)ethoxy]-3,5-diiodophenyl]methanone hydrochloride, and belongs to benzoyl derivatives. The polarographic behaviors of benzoyl derivatives such as fenofibrate, ketoprofen, amiodarone, mebendazole and flubendazole have been studied in aqueous and organic media and used for analytical purpose, [22][23][24][25][26] respectively. All these derivatives showed a polarographic reduction wave, which was attributed to the reduction of the electroactive benzoyl group via a two-electron and two-proton addition.…”
Section: Voltammetric Behavior Of Amiodaronementioning
confidence: 99%